2015
DOI: 10.17795/nmsjournal24453
|View full text |Cite
|
Sign up to set email alerts
|

How Baloch Women Make Decisions About the Risks Associated With Different Childbirth Settings in Southeast Iran

Abstract: Background: In Zahedan City in Southeast Iran, some women prefer to give birth at home despite the availability of the equipped hospitals and expert advice that hospital births are safer. Objectives: This study explains how Baloch women make decisions regarding the risks associated with childbirth at home versus a hospital. This study identifies and defines the factors that influence the choice of the place of delivery by Baloch women. Materials and Methods:The article draws on data from a grounded theory. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…For example, in the studies conducted by Vandecasteele et al and Ward et al the processes of theoretical sampling were not explained, and if yet so, researchers used different interpretations of theoretical sampling and its application method (12,13). Also, in two recent grounded theory studies, Moudi et al and Mirzaee Rabor et al used purposive sampling to select the study participants; however, they did not mention the employment of theoretical sampling in their studies (14,15). In the study by Masoudi Alavi et al through grounded theory, some sentences showed that selecting participants during the study was merely purposive and was not theoretical.…”
Section: Contextmentioning
confidence: 99%
“…For example, in the studies conducted by Vandecasteele et al and Ward et al the processes of theoretical sampling were not explained, and if yet so, researchers used different interpretations of theoretical sampling and its application method (12,13). Also, in two recent grounded theory studies, Moudi et al and Mirzaee Rabor et al used purposive sampling to select the study participants; however, they did not mention the employment of theoretical sampling in their studies (14,15). In the study by Masoudi Alavi et al through grounded theory, some sentences showed that selecting participants during the study was merely purposive and was not theoretical.…”
Section: Contextmentioning
confidence: 99%
“…Since 99% of these deaths occur in low- and middle-income countries, research is warranted to identify the root causes of maternal and infant safety issues and propose solutions to such issues in lower income countries ( 1 , 2 ). Pregnancy-related mortality is a serious health and social problem affecting many women and their families each year ( 3 - 6 ). Nurses working in maternity services believe that numerous problems can result in safety issues both for mothers and their babies in delivery rooms ( 7 - 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of our study on baloch women's decision making about childbirth settings ( 1 ), I noticed a letter about my published article in your journal ( 2 ) and I am very glad that this article has been helpful. Now, I want to mention some points in detail about my study.…”
mentioning
confidence: 99%